Cardiac Surgery for Ergotamine-Induced Multivalvular Heart Disease - Lazopoulos, George; Papaioannou, George; Kantartzis, Michael (The Thoracic and Cardiovascular Surgeon, 2013)
Ergotamine is used to abort or prevent vascular headache. Valvular heart disease as an adverse effect of long-term ergotamine therapy has been rarely reported in the English literature, with only a few cases published. It is hypothesized that ergot-derived agents stimulate serotonergic receptors (5-HT2B), causing proliferation of myofibroblasts, with subsequent thickening of valve leaflets and chords. This case presentation aims at increasing clinicians' awareness of this potential complication.
Keywords: ergotamine; cardiac valve; cardiac surgery